Staying hooked: effective science engagement and communication in recreational fisheries - Pita, Pablo; Tracey, Sean; Arlinghaus, Robert; Bachiller, Eneko; Pinho-Duarte, Filipa; Ferter, Keno; Henriques, Filipe; Hook, Samantha; Hyder, Kieran; Irigoyen, Alejo; Jiménez, María P.; Laporta, Martín; et al. (Frontiers in Marine Science, 2025)
● This abstract summarizes the results of two expert consultations conducted to gather insights into effective communication and engagement strategies in recreational fisheries.● Effective science communication fosters knowledge, understanding, and trust in both science and management decisions.● Public involvement and stakeholder engagement are essential for effective management.● Simplifying complex research findings and using diverse communication tools enhance awareness and understanding.● Strong communication strategies are necessary to implement sustainable recreational fisheries management frameworks.● Funding for communication efforts is often insufficient but remains crucial for success.● Participatory workshops and data-sharing arrangements enhance collaboration and involvement.● Multi-stakeholder consortiums and tailored communication strategies strengthen stakeholder engagement and promote adaptive governance. Interdisciplinary outreach and strategic social media use play vital roles in raising environmental awareness.